2018
DOI: 10.1021/acs.jpcc.7b08994
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Hopping Brings Lattice Strain and High Catalytic Activity in the Low-Temperature Oxidative Coupling of Methane in an Electric Field

Abstract: Detailed reaction mechanisms for the oxidative coupling of methane (OCM) over Ce 2 (WO 4 ) 3 catalysts at low temperatures in an electric field were investigated. The influence of Ce cations in the Ce 2 (WO 4 ) 3 catalyst was evaluated by comparing the OCM activity over various Ln 2 (WO 4 ) 3 (Ln = La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, and Dy) catalysts in an electric field. The electronic states of Ln and W cations and the relationship between the distorted Ce 2 (WO 4 ) 3 structure and methane activation were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 44 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The strain can be induced by various factors such as lattice mismatch, thermal coefficient mismatch, grain morphology, lattice distortions, and interlayer charge transfer. , The effect of thermal coefficient mismatch on strain can be excluded because the growth (deposition/annealing) temperature is the same for all the films. In the present study, the lattice distortion and charge transfer mechanism due to the internal field have a predominant contribution to the lattice strain than the other factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain can be induced by various factors such as lattice mismatch, thermal coefficient mismatch, grain morphology, lattice distortions, and interlayer charge transfer. , The effect of thermal coefficient mismatch on strain can be excluded because the growth (deposition/annealing) temperature is the same for all the films. In the present study, the lattice distortion and charge transfer mechanism due to the internal field have a predominant contribution to the lattice strain than the other factors.…”
Section: Resultsmentioning
confidence: 99%
“…This will be further corroborated from the FTIR, PL, and current–voltage ( I – V ) analysis. It is found that the heterostructure with t MoO 3 = 67 nm exhibits a maximum lattice strain which could be possibly due to the interfacial charge transfer and octahedral distortion . This will, in turn, reduce the charge carrier recombination rate which is vital for better photocatalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…However, at temperatures less than 600 °C, creation of active oxygen sites on MgO led to lower activity. Contrary, at low temperature, catalysts such as Ca-Sm 2 O 3 /MgO, Sm 2 O 3 /MgO, and Ca-CeO 2 /MgO exhibited higher yields than those of Li- and Na-based catalysts, due to less active site activation at lower temperature …”
Section: Natural Gas Flaring Utilization Technologiesmentioning
confidence: 91%
“…Similarly, the V D application can activate the active layer. In the case of the oxidative coupling of methane over cerium tungsten oxide catalysts, the reaction temperature was found to decrease when an electrical current flowed through the catalyst bed [30]. The proposed mechanism involves the activation of lattice oxygen through the oxidation of Ce cations, which enhances the ability of H abstraction from methane.…”
Section: Effects Of the Drain Voltage V Dmentioning
confidence: 99%